Sosialisasi Peranan Profesi Aktuaris pada Industri Asuransi dan Asuransi untuk Kehidupan kepada Masyarakat Cikarang - Maria Yus Trinity Irsan; Lina Rosmawati; Fauziah Nur Fahirah Sudding (President University, 2019)
Actuarial science study program is a new study program in Indonesia. Recently many universities in Indonesia have opened the study program. Currently, Indonesia needs more actuary, this is one of the reasons for the existence of the actuarial science study program in Indonesia. However, many Indonesians do not know about the actuary and actuarial science field. Besides that, most Indonesians have not realized the importance of insurance for our life. The socialization about actuary and insurance is one of the ways to introduce actuary and increase the insurance awareness to the people in Indonesia, especially in Cikarang. This event went by distributing pamphlet and giving a short explanation to the respondent about actuary, insurance, and the relationship between them.